Fluoroscopy-guided removal of individualised airway-covered stents for airway fistulas. Issue 9 (September 2018) - Bi, Y.; Chen, H.; Li, J.; Fu, P.; Ren, J.; Han, X.; Wu, G.
Abstract : Aim: To report the techniques and complications associated with fluoroscopy-guided removal of individual covered stents for airway fistula disease over a 6-year period. Materials and methods: A retrospective analysis was conducted of 85 patients, 72 male and 13 female, who underwent fluoroscopy-guided stent removal from January 2011 to June 2017. Patients ranged in age from 15 to 81 years (mean, 54.9±12.3 years). Before removal, 90 stents had been placed for airway fistula disease. All patients underwent diagnostic flexible bronchoscopy and airway computed tomography (CT) prior to stent removal. The indications for stent removal and post-interventional complications were analysed. Results: Eighty-nine of 90 airway stents were successfully removed from 85 consecutive patients, for a technique success rate of 98.9%. Of these, 14 stents showed strut fracture, one stent showed retained stent pieces, and the remaining 75 stents were removed in one piece. Indications for stent removal included regular removal ( n= 46), stent migration ( n= 11), excessive granulation tissue ( n= 10), strut fracture ( n= 4), intolerance of stenting ( n= 6). Complications of stent removal were as follows: retained stent pieces ( n= 1), mucosal tear with massive bleeding ( n= 2), re-obstruction requiring stenting ( n= 1), dyspnoea with mechanical ventilation needed ( n= 1), and dyspnoea with oxygen inhalation needed ( n= 1). Conclusions: Airway stents can be safely removed under fluoroscopy guidance. Removal after 31–90 days is recommended for removal to avoid excessive granulation tissue. Highlights: Techniques and complications of fluoroscopy-guided removal of airway stents were reported. We reported a high success rate with relatively low complication rates. Airway stent can be safely removed under fluoroscopy guidance. Removal after 31–90 days is recommended for airway stents.